Isolation and Identification of Dermatophytes Associated with Barbing Instruments in Ungogo Local Government Area, Kano State (Sahel Journal of Life Sciences FUDMA, 2026)
Dermatophytosis is a common superficial infection that affects people irrespective of regional differences all over the world. The aim of this research was to isolate and identify dermatophytes associated with barbing instruments in Ungogo Local Government Area of Kano State. In the methodology, swabs and scrapings associated with barbing saloons were collected as samples.  Direct microscopy was done using 10% potassium hydroxide (KOH) and the samples were also cultured on Sabouraud Dextrose Agar (SDA) for the isolation of the associated dermatophyte species. The result revealed an overall occurance of 53(13.8%) positivity rate with four different dermatophytic species (with Trichophyton rumbrum (41.5%), Trichophyton mentagrophytes (24.5%), Microsporum canis (17.0%), and Microsporum tonsurans (17.0) identified. The result also indicated that hair combs (66.0%) were more contaminated with damertophytes than clippers which had (34.0%). Contamination of instrument per species showed that T. rubrum had more occurrence on hair comb (63.7%) than clippers (36.4%); T. mentagrophyte also occurred more on hair comb (67%) than on clippers (33.3%). Similarly with T. tonsurans and M. canis were more isolated from hair comb than clippers. Dermatophytosis can easily be spread between individuals in barbing saloons, via the barbing instruments; Trichophytons and Microsporum species are of particular concern in the study area.